Stem cell-based therapeutic strategies for down syndrome and Alzheimer’s disease - Hamadelseed, Osama; Skutella, Thomas (Stem cell research & therapy, 2025)
Background: Down syndrome (DS) and Alzheimer’s disease (AD) are two distinct yet interconnected neurological conditions that share overlapping pathological features, including amyloid-beta plaque accumulation, neuroinflammation, and progressive neurodegeneration. Individuals with DS are at increased risk of developing AD-like dementia owing to the overexpression of the amyloid precursor protein-encoding gene on chromosome 21. Despite significant research efforts, effective disease-modifying treatments remain unavailable for both conditions, necessitating the exploration of novel therapeutic approaches. Methods: We analyzed and synthesized the existing literature on stem cell therapy as a treatment for DS and AD. We conducted a comprehensive search of PubMed, Google Scholar, and Web of Science databases, focusing on recent, high-quality, and peer-reviewed studies on stem cell therapy in DS and AD. Results: The findings indicate that stem cell therapy represents a promising therapeutic approach for both conditions. Preclinical trials using neural, mesenchymal, and induced pluripotent stem cells have shown their potential to mitigate disease pathology, restore neuronal function, modulate neuroinflammation, enhance neurogenesis, and improve cognitive performance in DS and AD models; these findings suggest the viability of stem cell-based interventions as a disease-modifying strategy. However, despite promising findings, the efficacy and safety of these approaches require further validation through well-designed human clinical trials before clinical translation. Furthermore, AD research in stem cell therapy is currently more advanced than DS research, with a greater number of preclinical and early clinical investigations. In fact, people with DS have been previously excluded from clinical trials. Conclusions: While both DS and AD share common neurodegenerative mechanisms and are potential candidates for stem cell therapeutic approaches, the therapeutic focus varies. This study underscores the potential of stem cell therapy as a novel disease-modifying approach for both conditions while emphasizing the need for further research to refine therapeutic protocols, address ethical and safety concerns, and evaluate the feasibility of translating these therapies into clinical practice.